The Role of Decision Strategies in Understanding Professionals' Susceptibility to Judgment Biases - Cuccia, Andrew D.; Gill, Gary A. Mc (Journal of Accounting Research, 2000)
Andrew D. Cuccia, Gary A. Mc Gill, The Role of Decision Strategies in Understanding Professionals' Susceptibility to Judgment Biases, Journal of Accounting Research, Vol. 38, No. 2 (Autumn, 2000), pp. 419-435